Collaborative marketing for the sustainable development of community-based tourism enterprises: a reconciliation of diverse perspectives. Issue 18 (8th November 2019) - Ngo, Tramy; Hales, Rob; Lohmann, Gui
ABSTRACT: Collaborative marketing for the sustainable development of community-based tourism enterprises (CBTEs) is subject to diverse stakeholder perspectives and a complex mix of factors determining collaboration success. This research investigates a framework supporting stakeholder collaborations in marketing CBTEs for sustainable development. The proposed framework is an outcome of the process of reconciling divergent perspectives in CBTE collaborative marketing using a knowledge co-production approach. Particularly, knowledge interactions between researchers and research participants to achieve a synthesis of perspectives in developing a collaborative marketing approach for the sustainable development of CBTEs in Vietnam were investigated. The knowledge interaction occurred in the form of a workshop that included 15 CBTE stakeholders and the first author and was undertaken in the village of Triem Tay (Vietnam). Through the workshop, a collaborative marketing framework for CBTE sustainability was identified. The framework stated the reasons for the divergence of perspectives on CBTE collaborative marketing for sustainable development: limited understanding of involved stakeholders; individuality in collective efforts; stakeholder self-righteousness; and contextual factors. Accordingly, the framework identified four attributes supporting stakeholders collaborations in marketing CBTEs for sustainable development: improved and right-directed perspectives of CBTE stakeholders; a set of rules governing stakeholder interventions; government involvement in CBTE collaborative marketing in the roles of an inspirer and an arbitrator; and the transformation from successful tour operators to social entrepreneurship to facilitate CBTE collaborative marketing. The contribution of this study lies in the potential of a knowledge co-production approach to be utilised in collaborative works involving multiple perspectives. Additionally, the study provides insights into the discussion of community-based tourism collaboration.